Structural Comparisons of Cefotaximase (CTX-M-ase) Sub Family 1 - Shurina, Ben A.; Page, Richard C. (Frontiers in Microbiology, 2021)
The cefotaximase, or CTX-M, family of serine-β-lactamases represents a significant clinical concern due to the ability for these enzymes to confer resistance to a broad array of β-lactam antibiotics an inhibitors. This behavior lends CTX-M-ases to be classified as extended spectrum β-lactamases. Across the family of CTX-M-ases most closely related to CTX-M-1, the structures of CTX-M-15 with a library of different ligands have been solved and serve as the basis of comparison within this review. Herein we focus on the structural changes apparent in structures of CTX-M-15 in complex with diazabicyclooctane and boronic acid transition state analog inhibitors. Interactions between a positive surface patch near the active site and complementary functional groups of the bound inhibitor play key roles in the dictating the conformations of active site residues. The insights provided by analyzing structures of CTX-M-15 in complex with diazabicyclooctane and boronic acid transition state analog inhibitors and analyzing existing structures of CTX-M-64 offer opportunities to move closer to making predictions as to how CTX-M-ases may interact with potential drug candidates, setting the stage for the further development of new antibiotics and β-lactamase inhibitors.